HUBUNGAN EXPLOSIVE POWER OTOT TUNGKAI DENGAN KECEPATAN LARI 60 METER SISWA KELAS VII SMP NEGERI 3 MANDAU - Mulyono, Andi; Saripin, Saripin; Agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study is a correlation research by connecting two different variables. the problem in this research is the low-speed run 60 meters distance students, it is because the explosive power of the legs at the time of running look less than optimal. This research aims to determine whether there is a relationship of explosive power leg muscle with a running speed of 60 meter class VII SMP Negeri 3 mandau, the number of samples as many as 30 people, based on the results of research that has been done in the seventh grade students of SMP Negeri 3 Mandau To determine the extent of the relationship between the explosive power leg muscle with a running speed of 60 meters, obtained r = 0.425 categorized enough. significance test using the formula t test of significance. The calculation results of t = 2.485 while t table = 1,701. so t = 2.45> t table = 1,701. it can be concluded as follows: the presence of a significant relationship between the explosive power leg muscle with a running speed of 60 meter class VII SMP Negeri 3 mandau accepted. based on the results of this study concluded that the hypothesis (Ho) reads: there is no significant relationship between the explosive power leg muscle (X) with a running speed of 60 meters (Y). Based on the analysis of test data obtained t and 2,485 t of means t> t table (1,701) thereby Ho refused and Ha is received, so that it can be concluded there is a relationship between the explosive power leg muscle with a running speed of 60 meters V11 junior high school students in grade 3 mandauÂ Keywords: explosive power leg muscle, running speed of 60 meters